Six issues and we keep going forward (Ozone Therapy Global Journal, 2016)
Doing a bit of history, I remember with nostalgia and affection the issue number zero of the Spanish Journal of Ozone Therapy published in May 2010, which was born with great enthusiasm and desire. In May 2011 we published the number 1 and since then up to today May 2016, without failure we have been fulfilling our annual appointment, incorporating scientific advances related to ozone therapy and maintaining a high scientific level. The journal has carved his way with great effort and professionalism making deservedly earn a place in the world of the science. It has been published for free 6 issues and 5 supplements (issue number 0 is not counted) with original high-impact scientific contents, in English and Spanish, faithfully respecting all international standards. It has been arduous tasks, which involved lot of time, dedication, energy, effort, wisdom, know-how and of course love for the therapy we use.Noteworthy is the lack of the journal. All the work of editing and of peer review is free, which has tremendous merit, because the time, knowledge and energy involved is huge.